Reproductive life course histories and menopausal outcomes at midlife: Evidence from the National Longitudinal Study of Adolescent to Adult Health - Brianah M McCoy; Stephanie M Koning; Kathleen Mullan Harris; Lauren Gaydosh (The Journals of Gerontology, Series B: Psychological Sciences and Social Sciences, 2026)
Abstract Objectives Menopause is a heterogeneous transition that varies in timing and type, yet population-based research rarely considers how reproductive life course experiences shape menopausal outcomes. This study examines whether reproductive timing, reproductive history, and reproductive health across adolescence and adulthood are associated with menopausal status, early menopause, and surgical menopause at midlife. Methods Using data from women in Waves I–VI of the National Longitudinal Study of Adolescent to Adult Health (Add Health), we constructed reproductive life course histories including pubertal timing, pregnancy and parity, reproductive complications, and gynecologic conditions. Menopausal outcomes at Wave VI included menopausal status, early menopause (before age 40), and surgical menopause. Survey-weighted logistic regression models estimated associations between reproductive characteristics and menopausal outcomes, adjusting for socioeconomic context and cumulative reproductive stress. Stratified analyses by pregnancy history assessed whether associations with gynecologic pathology were independent of fertility history. Results At Wave VI (mean age 44), 18% of women were postmenopausal. Among them, 69% reported surgical menopause and 60% experienced menopause before age 40, indicating a substantial prevalence of non-natural and early transitions. Pregnancy and parity were consistently associated with menopausal outcomes, whereas reproductive timing showed more limited associations. Gynecologic pathology was strongly associated with early and surgical menopause independent of pregnancy history. Discussion Menopause emerges as a life course process shaped by reproductive histories and midlife reproductive health. The high prevalence of early and surgical menopause underscores the importance of examining heterogeneous pathways to menopausal timing and type in population-based research.